2017
DOI: 10.1590/s1980-220x2016140903209
|View full text |Cite
|
Sign up to set email alerts
|

Associated factors to urinary incontinence in women undergoing urodynamic testing

Abstract: Objective: Analyzing factors associated with urinary incontinence (UI) among women submitted to urodynamic testing. Method: A cross-sectional study of 150 women attended at a urological center. Data were analyzed using univariate and multivariate statistics. Results: White women (79.3%), overweight (45.3%), menopausal (53.3%), who drink coffee (82.7%), sedentary (65.3%), who had vaginal birth (51.4%), with episiotomy (80%), and who underwent the Kristeller maneuver (69%). 60.7% had Urethral Hypermobility (UH).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
12

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 27 publications
(47 reference statements)
1
15
0
12
Order By: Relevance
“…Studies have shown UI as associated with diseases such as: infection of the urinary tract 11 , arterial hypertension 12 , diabetes mellitus 6,[12][13][14] , a history of cardiac disease 4 , obesity 4,6,10 , strokes 6,8,13,15 , respiratory problems 8,15 , depression 6 , cognitive deficit 16 , arthritis 12 , arthrosis/rheumatism 17 , prostatic hyperplasia 18 , a history of falls 4,17 , functional limitations, limited mobility or dependence 6,8,11,14,16,18 , comorbidity 19 and frailty 17 . in addition to these conditions, UI may be associated with lifestyle habits such as sedentiarism 20 . There is also an association with polypharmacy 8 , gynecological surgery, hysterectomies and the menopause in women 20 , a negative self-assessment of health status 9,15,17 and poor quality of life 19 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown UI as associated with diseases such as: infection of the urinary tract 11 , arterial hypertension 12 , diabetes mellitus 6,[12][13][14] , a history of cardiac disease 4 , obesity 4,6,10 , strokes 6,8,13,15 , respiratory problems 8,15 , depression 6 , cognitive deficit 16 , arthritis 12 , arthrosis/rheumatism 17 , prostatic hyperplasia 18 , a history of falls 4,17 , functional limitations, limited mobility or dependence 6,8,11,14,16,18 , comorbidity 19 and frailty 17 . in addition to these conditions, UI may be associated with lifestyle habits such as sedentiarism 20 . There is also an association with polypharmacy 8 , gynecological surgery, hysterectomies and the menopause in women 20 , a negative self-assessment of health status 9,15,17 and poor quality of life 19 .…”
Section: Introductionmentioning
confidence: 99%
“…in addition to these conditions, UI may be associated with lifestyle habits such as sedentiarism 20 . There is also an association with polypharmacy 8 , gynecological surgery, hysterectomies and the menopause in women 20 , a negative self-assessment of health status 9,15,17 and poor quality of life 19 .…”
Section: Introductionmentioning
confidence: 99%
“…• Perineal trauma and loss of pelvic floor strength; [22][23][24][25][26][27] • Risk of causing amniotic fluid embolism and lacerations of the anal sphincter; 25 • Risk of epidural hemorrhage; 30 • Cardiac changes in the newborn, asphyxia, hypoxemia, possible complications in his skeleton, in addition to Caput sucessaneum; [22][23][24][25][26]30 Some women may still be subjected to Kristeller's maneuver in unregulated obstetric institutions, many of these sites have not yet properly documented the occurrence of the maneuver during labor. This makes it difficult to access data on the number of patients undergoing the maneuver and what complications occur after its use, in addition to hurting the patient's rights since every intervention must be reported in the patient's medical record, especially the one that causes parturient pain and discomfort during its performance.…”
Section: Resultsmentioning
confidence: 99%
“…[22][23][24][25][26] This compressive technique is considered harmful to obstetric care, considering that it is considered an invasive procedure and is related to the inadequate conduct of labor, which causes complications, such as perineal trauma for the mother, so it must be thus avoided. 27 Despite this, there are still those who believe that this practice contributes to accelerate the expulsive period of women in childbirth, being still widely used as an obstetric maneuver. The practice of this practice, in a common way, is an activity that must be abandoned.…”
Section: Resultsmentioning
confidence: 99%
“…Apesar da IU ser uma condição desconfortável e, muitas vezes, constrangedora, que causa limitações e/ou alterações nas atividades sociais, ocupacionais e domésticas, é observado uma certa negligência quanto a busca por tratamento de tais disfunções, visto que muitas mulheres consideram tal fator como uma condição "natural", demonstrando desconhecimento acerca do assunto 4,5 .…”
Section: Introductionunclassified